2020
DOI: 10.3390/microorganisms8081110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Immunochromatographic Test Strip for Serological Detection of Bovine Babesiosis in Uganda

Abstract: In Uganda, bovine babesiosis continues to cause losses to the livestock industry because of shortages of cheap, quick, and reliable diagnostic tools to guide prescription measures. In this study, the presence of antibodies to Babesia bigemina and Babesia bovis in 401 bovine blood samples obtained from eastern and central areas of Uganda were detected using enzyme-linked immunosorbent assays (ELISAs) and immunochromatographic test strips (ICTs). The ELISA and ICT test used targeted the B. bigemina C-terminal rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…ELISA allows processing of a higher number of samples in a working day, and since it is an automated method, another advantage is the objectivity of the results interpretation [ 12 ]. Among the main disadvantages of ELISA is that the procedure involves several steps for execution, which makes it costly, and like IFAT, it requires special laboratory equipment for sample analysis and result interpretation [ 14 ]. Recently, the development of new and innovative diagnostic methods, such as an immunochromatography test (ICT) based on a lateral flow membrane, have changed the landscape for users, facilitating the detection of antibodies or soluble antigens [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ELISA allows processing of a higher number of samples in a working day, and since it is an automated method, another advantage is the objectivity of the results interpretation [ 12 ]. Among the main disadvantages of ELISA is that the procedure involves several steps for execution, which makes it costly, and like IFAT, it requires special laboratory equipment for sample analysis and result interpretation [ 14 ]. Recently, the development of new and innovative diagnostic methods, such as an immunochromatography test (ICT) based on a lateral flow membrane, have changed the landscape for users, facilitating the detection of antibodies or soluble antigens [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seroprevalence rates in Uganda using ELISA and ICT based on SBP-4 protein were 6.2 and 4.3%, respectively [ 14 ], whereas in Indonesia, Babesia prevalence rates were 69.8 and 65.1%, and other studies reported seroprevalence rates of 28.4% and 25.3%, respectively [ 15 , 17 ]. In Argentina, using only the ICT, the determined seroprevalence of B. bovis was 71.3% [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In veterinary medicine, lateral flow immunoassays have been developed for various purposes; detection of diseases in companion and farm animals to achieve better results in the care and development of animals, for example, Parvovirus 21 , Newcastle 22 , Avian infectious bronchitis virus 23 , African swine fever 24 and Babesiosis 25 , The rapid detection of these diseases reduces the economic losses. Immunochromatographic methods have also been developed to detect antibiotics and analogs in milk 26 , which is greatly important for food safety.…”
Section: Discussionmentioning
confidence: 99%
“…Galegine was found to reduce blood glucose in humans in 1920, but proved to be very toxic 29 . Later, two derivatives of galegine, phenformin and metformin, were identified and introduced in the clinical use for the management of T2DM in the 1950s 29,31 . Phenformin was withdrawn from the market due to toxic adverse effects, leaving only metformin in use 29,32 .…”
Section: Introductionmentioning
confidence: 99%